2014
DOI: 10.1186/preaccept-1222589269130881
|View full text |Cite
|
Sign up to set email alerts
|

Role of nerve growth factor and its TRKA receptor in normal ovarian and epithelial ovarian cancer angiogenesis

Abstract: In normal ovarian function a controlled angiogenesis is essential. Several growth factors are involved in this process, such as the vascular endothelial growth factor (VEGF) and nerve growth factor (NGF). The angiogenesis process in the normal ovary is a tightly controlled process that occurs in each ovarian cycle. Also, angiogenesis is critical for ovarian cancer development and it is responsible for tumor spread, metastasis and its peritoneal dissemination. Ovarian cancer is the fifth leading cause of cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…In ovarian cancer, characterized by high levels of angiogenesis, this process is mostly driven by VEGF, a pro-angiogenic molecule overexpressed in most solid tumors (43). Another pro-angiogenic molecule overexpressed in ovarian cancer is NGF, which acts directly on endothelial cells and also on cancer cells, inducing them to increase their VEGF expression and secretion (12). In the present study, we found that NGF increases CRT levels (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In ovarian cancer, characterized by high levels of angiogenesis, this process is mostly driven by VEGF, a pro-angiogenic molecule overexpressed in most solid tumors (43). Another pro-angiogenic molecule overexpressed in ovarian cancer is NGF, which acts directly on endothelial cells and also on cancer cells, inducing them to increase their VEGF expression and secretion (12). In the present study, we found that NGF increases CRT levels (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…The normal active ovary undergoes angiogenesis at regular intervals; in ovarian cancer, there are disturbances in the normal angiogenic regulation, including alteration of the proangiogenic molecules such as NGF and the vascular endothelial growth factor (VEGF) expression. besides, the normal ovary expresses NGF and TRKA in granulosa cells, and NGF induces the proliferation of granulosa and theca cells (12). On the other hand, NGF levels are elevated and induce angiogenesis through its high affinity receptor TRKA by acting directly on endothelial cells and by stimulating VEGF production in epithelial cells in EOC (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Furthermore, NGF has been shown to act directly on tumor cells as well as indirectly on endothelial cells to promote angiogenesis. 14 Of note, activation of the TrkA receptor on endothelial cells induces vascular endothelial growth factor (VEGF) synthesis in EOC explants, a growth factor that promotes angiogenesis by acting on endothelial cells. 11,14 Despite the demonstrated importance of NGF and TrkA in EOC progression, these molecules cannot be considered as therapeutic targets because they play important roles in several tissues, mainly in the development and maintenance of the central and peripheral nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell described in such cancer depends on markers of "stemness" such as CD44, CD133, CD117, ALDH1A1, and EpCAM. Whereas there are many attempts to see characteristics of such stem cell in relation to NGF and FSHR [4][5][6]. Some other are trying to look at the metabolic reprogramming of cancer and cancer stem cells driven by genetic alterations which could be therapeutically targeted [7].…”
Section: Introductionmentioning
confidence: 99%